Gastrointestinal Conditions in Children With Severe Feeding Difficulties. (April 2019) - Rivera-Nieves, Desiree; Conley, Anita; Nagib, Keri; Shannon, Kaiya; Horvath, Karoly; Mehta, Devendra
Feeding aversion in children may progress to severe feeding difficulties. While oral-motor and sensory issues are usually the leading causes, organic etiologies should be considered. This study aimed to assess the prevalence of gastrointestinal conditions in children with severe feeding difficulties. We conducted a retrospective study of 93 children requiring an intensive feeding program. The medical records, radiologic and diagnostic tests, use of gastric tube feedings, preexisting medical conditions, and medications were reviewed. Fifty-two percent (52%) had esophagitis, 26.2% gastritis, and 40.7% lactase deficiency in upper endoscopy. In those who underwent an upper endoscopy, 26% of patients that were also tested for small intestinal bacterial overgrowth were found to be positive. Allergy testing was abnormal in 56.6% of those tested, while 27.5% and 75% had abnormal gastric emptying times and pH impedance results, respectively. Constipation was present in 76.3%. Thirteen of 32 were weaned off tube feedings. We conclude that gastrointestinal conditions are common in children with feeding disorders and should be investigated prior to feeding therapy.